2003
DOI: 10.1002/jsfa.1391
|View full text |Cite
|
Sign up to set email alerts
|

Quality characteristics of refined, bleached and deodorized palm olein and banana chips after deep‐fat frying

Abstract: The changes in quality characteristics of refined, bleached and deodorized (RBD) palm olein used for deep-fat frying of banana chips (180 • C for 3 min at 17 min intervals for 2 h day −1 , to give six fryings per day and 30 fryings over five consecutive days) were studied. Four frying systems were used: RBD palm olein without antioxidant (system 1); RBD palm olein with 0.2 g kg −1 α-tocopherol (system 2); RBD palm olein with 1 g kg −1 oleoresin rosemary (system 3); and RBD palm olein with the combination of 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Xu et al found correlations between colour and times of heating and frying of five modified rapeseed oils, sunflower oil and palm olein. Similar results have been obtained by other authors for French fries . Krokida et al noted that the proportion of red and yellow colour increased with increased duration of cyclic frying.…”
Section: Resultssupporting
confidence: 89%
“…Xu et al found correlations between colour and times of heating and frying of five modified rapeseed oils, sunflower oil and palm olein. Similar results have been obtained by other authors for French fries . Krokida et al noted that the proportion of red and yellow colour increased with increased duration of cyclic frying.…”
Section: Resultssupporting
confidence: 89%
“…They were then lightly blotted dry with tissue paper and sliced to a thickness of 2 mm using a mechanical slicer, before being weighed into 150 g batches for frying. RBD palm olein (4.5 kg) was used as the frying medium, supplemented with oleoresin rosemary (1 g) in accordance with Che Man et al 6 The temperature was raised to 180 ± 5 °C in 20 min and the batches of raw bananas were fried for 3 min. The fried banana chips were allowed to cool and were then packed (100 g each) in the four different packaging materials (LAF, OPP, PP and LDPE) using an ARSH‐300 Impulse Sealer (Arrow Brand, Perniagaan Timbang Dan Sukat Ban Hing SB, Selangor, Malaysia).…”
Section: Methodsmentioning
confidence: 99%
“…Green Abu bananas fried in refined, bleached and deodorised palm olein have been found to show good quality 5. 6…”
Section: Introductionmentioning
confidence: 99%
“…A combination of OR (0.065%), OS (0.071%), and citric acid (0.043%) was found to offer optimal synergistic protection against palm olein deterioration during frying [11]. Che Man et al [12] found that the addition of OR (0.1%) stabilized refined palm olein during deep-fat frying of banana chips for 10 h. The addition of a commercial rosemary extract (0.4%) also inhibited the deterioration of an oil mixture containing cottonseed oil, palm oil and sunflower oil (SO) during pan-frying of potatoes [13]. Vekiari et al [14] reported that oregano extracts effectively retarded the deterioration of vegetable oils heated at frying temperatures.…”
Section: Introductionmentioning
confidence: 99%